Kesadaran Hukum Masyarakat Dalam Pendaftaran Tanah-Tanah - Adi Israfil Fahrurrahman (Lembaga Penelitian dan Pendidikan Mandala, 2020)
The purpose of this study was to determine and analyze the legal awareness of the community in the registration of customary land rights, with location points in two villages, namely Desa Doridungga and Desa O'O in Donggo District, Bima-NTB Regency, in the perspective of Land law and and analyzing the obstacles faced by communities in registering customary land rights at the Bima District Land Office. The research method used is a Socio-legal research that is oriented to a value approach (value-oriented approach). Empirical / sociological research is used to find out what and how public awareness in registering customary land rights is related to the implementation of land registration in the Land Agency Office of Bima-NTB Regency. The results of the research conducted were the level of community legal awareness in the context of registering customary land rights in Bima Regency, generally and in particular, Donggo District. This is due to the lack of several aspects, namely, lack of legal knowledge, legal understanding, legal attitudes, and community behavior patterns. The obstacle faced by the people of O’O Villagers and Desa Doridungga in registering customary land rights is the lack of socialization from the local government regarding proper procedures for registering customary land rights. As well as the level of legal awareness of the villagers of O'O and Desa Doridungga to carry out sporadic land registration as a result of the wrong mindset about the importance of land registration